Analisis Semiotika Roland Barthes Pada Batik Besurek Dalam Konteks Komersialisasi - Saputra, Anggo Ahmad; Justian, Repi; Sari, Santi Purnama (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Batik besurek is an Indonesian intangible cultural heritage from Bengkulu Province with Arabic Malay calligraphy motifs. Initially, this cloth contained sacred philosophical-religious meanings and was used in traditional contexts. This study analyzes Batik besurek in the context of modern commercialization, which is motivated by the tension between the preservation of cultural heritage and market demands that risk eroding these fundamental values. The research aims to identify forms of shifting symbolic meanings, analyze driving factors, and reinterpret symbolic constructions among producers and consumers. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews with artisans, designers, and business actors, and documentation studies. Data analysis used Roland Barthes' semiotics to describe the denotative, connotative, and mythical meanings of commercial Batik besurek products. The results show a shift in meaning from sacred values ​​to aesthetic and economic values. Driving factors include market pressures, digital marketing strategies, and designers' interpretations of tradition. The study's conclusion underscores that commercialization has the potential to degrade the cultural meaning of Batik besurek despite its positive economic impact. These findings provide important input for stakeholders in formulating sustainable conservation strategies.